Morphological studies and meiotic chromosome analysis of Epimedium elatum (Morr & Decne) - Rare endemic medicinal plant of Northwestern Himalayas in India. - Lone, Sajad Ahmad; Hassan, Qazi Pervaiz; Gupta, Suphla; Mushatq, Saleem; Sultan, Phalisteen; Bedi, Yashbir Singh (Current Botany, 2017)
Epimedium elatum (Berberidaceace) is a rare endemic medicinal herb of Northwestern Himalayas in India. Recent ethnopharmacological reports have demonstrated its traditional medicinal use against various bone related diseases in the Kashmir Himalayas. It owes its pharmaceutical importance due to high concentration of flavonoid glycosides like Epimedin A, B, C and Icariin which are known mainly for aphrodisiac, antiosteoporosis, anticancer, antioxidant, antiaging, antifatigue and antiviral activities. It is a neglected medicinal plant in Northwestern Himalayan region and may fall in the list of endangered species due to continuous anthropogenic pressures in its native habitats. In this study, we investigated distributional and altitudinal range of this prized species from twenty diverse eco-geographical zones of Kashmir Himalayas for the first time. We also report here its diversity in morphological attributes both in wild and captive cultivation. The species has a very small population size in most of the surveyed habitats with no natural protection. Under cultivation it showed increased plant height (63.09±4.9cm), more number of leaves (95.53±11cm) and flowers (160.76±20cm), indicating importance of high altitude medicinal garden for its immediate ex situ conservation. Further, the acetocarmine staining and squashing of young anthers confirmed it as a diploid species (2n=12) like other Epimedium species. Chromosome number and meiotic abnormalities are also reported for the first time in the species. Finally, constant anthropogenic pressures in Northwestern Himalayas demand immediate in situ and ex situ conservation programmes for E.elatum.